Regeneration of earthworm populations in a degraded soil by natural and planted fallows under humid tropical conditions - Tian, G.; Olimah, J.; Adeoye, G.; Kang, B. (Wiley, 2000)
Earthworm populations (predominantly Hyperiodrilus africanus and Eudrilus eugeniae) were sampled monthly for 1 yr during 1994 and 1995 in natural regrowth vegetation fallow (dominated by the natural fallow shrub Chromolaena odorata L.), planted fallow (the woody species Senna siamea Lam., Leucaena leucocephala Lam., and Acacia leptocarpa), and intercropped maize (Zea mays L.)–cassava (Manihot esculenta Crantz) established in 1989 in a degraded Alfisol (Oxic paleustalf) in southwestern Nigeria. Compared to leaves of Chromolaena (3.3% N), N concentrations were lower in those of Senna and Acacia, and higher in Leucaena Acacia and Leucaena had higher polyphenol relative to the natural fallow (2%). The lignin was lower in Leucaena than the natural fallow leaves (14%). For 65% of the sampling dates, earthworm numbers under all fallows were significantly higher than under continuous maize–cassava. The mean earthworm numbers (no. m−2) during the rainy season (April–October) decreased in the following order: Chromolaena (147), Senna (131), Leucaena (92), Acacia (80), and maize–cassava (14). Earthworm fresh weights in fallow plots were higher than in the maize–cassava plot, though this was significant for only 4 out of 11 sampling dates. Higher earthworm numbers and biomass in fallow plots were attributed to higher litterfall, lower soil temperature, and higher soil moisture. The mean earthworm numbers were directly correlated with the mean soil moistures (r2 = 0.80, P < 0.05) in fallow plots and N/polyphenol ratios of fallow litterfall (r2 = 0.95, P < 0.05). Increase in earthworm population by fallows led to an increase in leaf-litter decomposition, soil organic matter, available P, and extractable cations and pH; and a decrease in soil bulk density and penetrometer resistance in the fallow plots.